2014
DOI: 10.14202/vetworld.2014.248-252
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Algerian honey on subclinical mastitis pathogens isolated from goat's milk

Abstract: Aim: The aim of the present study was to determine the susceptibility of subclinical mastitis pathogens isolated from goat's milk and to evaluate the antimicrobial activity of Algerian honey on mastitis causing bacteria. Materials and Methods:The antibacterial activity against the isolated bacteria was evaluated by determining the Minimal Inhibitory Concentration (MIC), using the agar incorporation method. Results:The results showed that both Micrococcus spp. and Klebsiella spp. were susceptible to Streptomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…High level of Erythromycin resistance was also reported in many previous studies as Isnel and Kirkan, (2012) 65% from goats, Bourabah et al, (2014) 66.66% in Tiaret province and El Ayis and Fadlalla, (2017) 80% from ewes, as well as a very high level of resistance to Cefoxtin was detected by another investigator Barbour et al, (2015) who found different percentage of resistance B-lactam antibiotics Cephalothin, Cefotaxime and Cefoxitin with 100%, 97% and 21% respectively.…”
Section: Discussionsupporting
confidence: 74%
“…High level of Erythromycin resistance was also reported in many previous studies as Isnel and Kirkan, (2012) 65% from goats, Bourabah et al, (2014) 66.66% in Tiaret province and El Ayis and Fadlalla, (2017) 80% from ewes, as well as a very high level of resistance to Cefoxtin was detected by another investigator Barbour et al, (2015) who found different percentage of resistance B-lactam antibiotics Cephalothin, Cefotaxime and Cefoxitin with 100%, 97% and 21% respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Among those 43 (56.58%) were from right quarters whereas the remaining 33 (43.42%) were detected with sub-clinical mastitis from left quarters (Pirzada et al 2016). In research in Tiaret Region (Western Algeria), milk samples were collected from 298 lactating goats in which the Californian Mastitis Test showed a prevalence of 33.9% among the tested goats (Bourabah et al 2013) (6) . McDougall et al (2002) (10) reported a prevalence of SCM at 19.0% and a similar result was obtained by Contreras et al (2007) (11) who noticed a prevalence of SCM from 5-30% in goats.…”
Section: Objectivesmentioning
confidence: 99%
“…Poor management and hygiene practices, teat injuries, and faulty milking machines are some predisposing factors that hasten the entry of the infectious agents and the course of the disease (Zenebe et al, 2014). Enterobacteriaceae such as coagulase negative Staphylococci (Bourabah et al, 2013), mycoplasma such as Mycoplasma mycoides subspecies capri (Egwu et al, 1999;Kumar et al, 2013), yeast, and other fungi such as Aspergillus niger (Al-Muhna, 2014) have been reported to be responsible for mastitis in animals.…”
Section: Introductionmentioning
confidence: 99%